Financial Situation of Residents of Simbirsk in Second Half of 19th — Early 20th Centuries - R. A. Muchamedov; A. V. Karpov (Научный диалог)
The financial situation and incomes of Simbirsk residents of the second half of the 19th — early 20th centuries are considered. The relevance of the study is due to the fact that understanding urban everyday life is impossible without an idea of the income that the citizens had. It is noted that in the period under review, class division is gradually turn to the division of society in the capitalist way, differentiation by income is confirmed, which is reflected in the mentality and administrative management. The difference between the population of Simbirsk and other Volga cities is shown: the share of the nobility among the urban population was twice as high as in neighboring cities, and the share of the peasantry was half that in Samara and four times less than in Saratov. A review of statistical information on the income of various classes and categories of employment is carried out. Particular attention is paid to the development of entrepreneurship and merchants and income in this area. It is noted that in Simbirsk, the development of entrepreneurship was slower than the average Russian values. The results of a comparative analysis of the standard of living and material situation of citizens living in Simbirsk with the indicators of other cities are presented. It is stated that for the sustainable development of capitalist relations, the introduction of financial organizations and entrepreneurship from the outside was necessary in Simbirsk.